RESEARCH OF THE SOFTWARE SECURITY MODEL AND REQUIREMENTS - Serhii Semenov; Viacheslav Davydov; Daryna Hrebeniuk (Сучасні інформаційні системи, 2021)
The subject of research in the article is a software security model. The aim of the work is to research the quality characteristics of the software and requirements for the software security in order to improve their safety. The article solves the following tasks: researching the shortcomings of the existing security model in order to identify its main shortcomings; study of the quality characteristics of software that affect its security in order to identify the possibility of improving the quality of software. The following results were obtained: on the basis of the analysis of the existing model of software security, the main features of the attributes of this model were identified, their advantages and disadvantages were given. On the basis of the conducted analytical study, the necessity of improving the existing model of ensuring the security of software has been proved. Existing requirements for software and characteristics that affect its quality are considered. The characteristics of software security are highlighted, the indicators of which should be improved. Conclusions: a software security model has been studied. The need to develop this model is shown by introducing the possibility of adapting the existing requirements for the security of software tools throughout the entire life cycle of software development; the study of the quality characteristics of software showed that to ensure its security, it is necessary to improve the following characteristics: integrity, authentication, confidentiality, access control. However, it was shown that an increase in these characteristics can lead to a deterioration in other indicators of software quality: portability, maintainability, performance.